Preaching and popular Christianity reading the sermons of John Chrysostom - Cook, James Daniel 1987- (Oxford University Press, 2019)
This study reassess how we read Chrysostom's sermons, with a particular focus on the stern language which permeated his preaching, and on which the image of the contrary congregation is largely based. In doing this, it recovers a neglected portrayal of Chrysostom as a pastor and of preaching as a pastoral and liturgical activity
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Johannes -- Chrysostomus -- 344-407; Volksfrömmigkeit; Predigt; John Chrysostom / Saint / -407 / Sermons / Criticism and interpretation; John Chrysostom / Saint / -407; Sermons; Criticism, interpretation, etc